2018
DOI: 10.1074/jbc.r117.001324
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-2 motors: Kinetics and biophysics

Abstract: Kinesin-2s are major transporters of cellular cargoes. This subfamily contains both homodimeric kinesins whose catalytic domains result from the same gene product and heterodimeric kinesins with motor domains derived from two different gene products. In this review, we focus on the progress to define the biochemical and biophysical properties of the kinesin-2 family members. Our understanding of their mechanochemical capabilities has been advanced by the ability to identify the kinesin-2 genes in multiple spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 106 publications
3
26
0
1
Order By: Relevance
“…2A) with rates k1 = 1.3 s -1 and k2 = 0.44 s -1 (A1 = 0.68, A2 = 0.32; Table 1). The ~30-fold difference in stepping rates between KIF3AA and KIF3CC is consistent with previous single-molecule velocity reports (4,14).…”
Section: Kif3aa Kif3ac and Kif3cc Step Dwell Times And Backsteppingsupporting
confidence: 91%
See 2 more Smart Citations
“…2A) with rates k1 = 1.3 s -1 and k2 = 0.44 s -1 (A1 = 0.68, A2 = 0.32; Table 1). The ~30-fold difference in stepping rates between KIF3AA and KIF3CC is consistent with previous single-molecule velocity reports (4,14).…”
Section: Kif3aa Kif3ac and Kif3cc Step Dwell Times And Backsteppingsupporting
confidence: 91%
“…A recent study suggested that scaling of total force generation with the number of motors may happen more efficiently for kinesin-2 motors than in other kinesin subfamilies, suggesting that these motors may be adapted to drive transport in larger teams (54). The high probability of KIF3AC detachment from the microtubule under load along with the fast microtubule association kinetics of KIF3AC (4,17,18) would enable KIF3AC to navigate obstacles on the microtubule effectively (55) or transport cargo more efficiently in larger ensembles (56), (57,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kinesin‐2 family consists of two KIF3 heterodimers, KIF3AB and KIF3AC, and the homodimeric KIF17 . Kinesin‐2s have been proposed to participate in axonal and dendritic transport, but their neuronal cargoes and transport characteristics are not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Among the wide family of kinesins, Kinesin-2 is a plus end directed transporter made of two motor subunits, KIF3A and KIF3B, and a cargo-binding subunit, KAP3 [ 9 , 10 , 11 ]. During embryonic development, Kinesin-2, by translocating multiprotein particles intraciliary, allows the formation of motile primary cilia, which in turn determine the acquisition of left-right asymmetry [ 11 , 12 , 13 ]. Furthermore, intraflagellar transport by KIF3A is also required for the Hedgehog signal transduction cascade [ 14 ].…”
Section: Introductionmentioning
confidence: 99%